Heavy metals concentration in the selected commercially local shrimp species from Sarawak river - Nur Syuhadah, Binti Kamarozaman (Universiti Malaysia Sarawak (UNIMAS), 2014)
The upsurge of riverine system contamination of heavy metals from industrialization and urbanization become a global concern as it tend to contaminate the water and bioaccumulate in the aquatic organisms including shrimps. Four local shrimp species namely Macrobrachium rosenbergii (Male), Macrobrachium rosenbergii (Female), Macrobrachium sp. and Metapenaeus sp. originally from Sarawak River were assessed to detennine the heavy metals concentration. Shrimp samples were digested with concentrated HNO) (63%) and HCI (37%) on the hot plate before the selected metals were analyzed by using Flame Atomic Absorption Spectrophotometer (F AAS) and Flow Injection Mercury System (FIMS). The high range concentrations of Zinc were 30.60 - 161.52 mglkg in Macrobrachium rosenbergii (Male), Copper were 16.99 - 711.80 mglkg in Macrobrachium sp., Cadmium were range from below detection limit (BDL) - 12.47 mglkg in Metapenaeus sp., Lead were in range of 0.23 - 20.07 mglkg in Macrobrachium rosenberg;; (Female) and Mercury were in range of 0.03 - 9.78 mglkg in Metapenaeus sp. The heavy metals concentration showed no significant difference (p>O.05) among the shrimp species however significant difference (p<O.05) were determined among the body parts. The distribution pattern of heavy metals accumulation for all species exhibited as follows: Cu>Zn>Pb>Cd>Hg. The tendency of metals accumulated in different parts showed the following trend: hepatopancreas > gills > abdominal muscle > exoskeleton. It showed that all Macrobrachium species accumulated considerable level of heavy metals followed by Metapenaeus sp. The recorded total concentration of Zn, Co, Cd, Ph and Hg were exceeded the permissible limit recommended by FAOIWHO (1992) reflected the unhealthy environment of Sarawak River.